The design of interactive conversation agents - Goh, Ong Sing; Fung, C.C. (World Scientific and Engineering Academy and Society, 2008)
Interactive conversation agents or CAs are computer programs or application software designed to simulate conversation with one or more human users in natural language. Providing CAs with knowledge, intelligence and humanoid interface has allowed them to be used in several practical applications. This paper presented the development and its performance of the interactive CAs called Artificial Intelligent Naturallanguage Identity or AINI.